Structural steelwork design to BS 5950 - Morris, L.J (Longman, 1996)
This student text deals with design at an elementary level, familiarising the reader with BS 5950, then proceeds to cover all aspects of the design of whole buildings, highlighting the integration of elements to produce economic, safe structures.